2015
DOI: 10.1371/journal.pone.0142834
|View full text |Cite
|
Sign up to set email alerts
|

ICAM1 Is a Potential Cancer Stem Cell Marker of Esophageal Squamous Cell Carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) accounts for about 90% of esophageal cancer diagnosed in Asian countries, with its incidence on the rise. Cancer stem cell (CSC; also known as tumor-initiating cells, TIC) is inherently resistant to cytotoxic chemotherapy and radiation and associates with poor prognosis and therapy failure. Targeting therapy against cancer stem cell has emerged as a potential therapeutic approach to develop effective regimens. However, the suitable CSC marker of ESCC for identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 47 publications
(40 reference statements)
0
39
0
Order By: Relevance
“…We also identified that CD54 + prostate cancer cells show characteristics of CSCs both in vitro and in vivo . Recent studies also showed that CD54 is a potential CSC marker of esophageal squamous cell carcinoma 44, glioblastoma 45, and prostate cancer 45. Together, these data suggested that CD54 was a reliable marker for CSCs.…”
Section: Discussionmentioning
confidence: 83%
“…We also identified that CD54 + prostate cancer cells show characteristics of CSCs both in vitro and in vivo . Recent studies also showed that CD54 is a potential CSC marker of esophageal squamous cell carcinoma 44, glioblastoma 45, and prostate cancer 45. Together, these data suggested that CD54 was a reliable marker for CSCs.…”
Section: Discussionmentioning
confidence: 83%
“…Reduced expression of ICAM-1 could play a role in the suppression of tumor progression in many cancer cells, such as breast cancer (Ogawa et al, 1998), gastric cancer (Fujihara et al, 1999), lung cancer (Kotteas et al, 2014) and colorectal cancer (Maeda et al, 2002). Additionally, ICAM1 and CD44 may have compensatory effects to maintain the dry characteristics of esophageal squamous cell carcinoma, indicating multiple targeted therapies that can be combined and considered in cancer treatment (Tsai et al, 2015). Research has demonstrated that ICAM1 is involved in angiogenesis through the regulation of endothelial cell migration (Kevil et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…ICAM1, a member of the immunoglobulin superfamily (IGSF), is an important adhesion molecule (24) involved in cell metastasis, differentiation and proliferation. Recently, ICAM1 was reported to serve as a liver cancer and ESCC stem cell marker (25,26); it can also promote ESCC epithelial-to-mesenchymal transition (EMT) (27) and cause metastasis of ESCC cells by regulating the expression of tumor metastasis-related genes, such as P53 (26). We predicted the possible role of ICAM1 as a target gene for lncRNA-ECM according to bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%